1998
DOI: 10.1046/j.1365-313x.1998.00219.x
|View full text |Cite
|
Sign up to set email alerts
|

Cell‐to‐cell transport of proteins: requirement for unfolding and characterization of binding to a putative plasmodesmal receptor

Abstract: SummaryPlasmodesmata and the nuclear pore complex (NPC) mediate the selective trafficking of proteins and protein-nucleic acid complexes. The events underlying the translocation of endogenous and viral proteins through plasmodesmata were investigated to further explore the parallels between these cell-to-cell and intracellular communication systems. Studies performed with crosslinked KNOTTED1 (KN1) revealed that a conformational change is required for the cell-to-cell movement of this protein. Microinjection o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 108 publications
(91 citation statements)
references
References 40 publications
3
87
0
Order By: Relevance
“…So far, studies using viral MPs and rice phloem proteins suggest that recognition by the PD trafficking machinery involves structural motifs (Haywood et al, 2002;Ishiwatari et al, 1998), though a short sequence motif appears to control the trafficking of the heat shock cognate 70 chaperone (Aoki et al, 2002). In the case of KN1, a short peptide, homologous to a region near the N terminus of the protein, can interfere with its trafficking, though it is not known whether this sequence motif is sufficient for trafficking (Kragler et al, 1998).…”
Section: Developmental and Tissue-specific Control Of Kn1 Traffickingmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, studies using viral MPs and rice phloem proteins suggest that recognition by the PD trafficking machinery involves structural motifs (Haywood et al, 2002;Ishiwatari et al, 1998), though a short sequence motif appears to control the trafficking of the heat shock cognate 70 chaperone (Aoki et al, 2002). In the case of KN1, a short peptide, homologous to a region near the N terminus of the protein, can interfere with its trafficking, though it is not known whether this sequence motif is sufficient for trafficking (Kragler et al, 1998).…”
Section: Developmental and Tissue-specific Control Of Kn1 Traffickingmentioning
confidence: 99%
“…One possible mechanism would be if KN1 was modified and gained a novel function during intercellular movement. Partial unfolding of KN1 is required for passage through PDs (Kragler et al, 1998), and could expose KN1 to post-translational modification(s). Alternatively, the lack of a KNOX overexpression phenotype in the 35S-GUS~KN1 plants could be because the fusion of GUS inhibits the ability KN1 to interact with partner proteins, such as Arabidopsis homologs of KN1 interacting protein (KIP), a BEL1-like TALE homeodomain protein (Smith et al, 2002).…”
Section: Biological Function Of Knox Homeodomain Protein Traffickingmentioning
confidence: 99%
“…Tag-MPB2C lib was overexpressed from plasmid pRSETA-⌬1-197MPB2C, and western-blot analysis of tag-MPB2C lib was done according to the manufacturer's protocol (Invitrogen, Carlsbad, CA). Conditions for renatured blot overlay assay are based on previously described dot-blot assays (Kragler et al, 1998). In brief, MP30 and CMV3a were blotted onto nitrocellulose membranes, treated twice for 15 min at room temperature with incubation buffer (40 mm HEPES, pH 6.8, and 10% [v/v] glycerol) containing 0.2% (v/v) Triton X-100 and Complete Protease Inhibitor Cocktail Tablets (Roche Diagnostics).…”
Section: In Vitro Interaction Of Mpb2c and Mp30mentioning
confidence: 99%
“…So far, a cell wall-associated pectin methyl esterase (PME; Dorokhov et al, 1999;Tzfira et al, 2000) was shown to specifically interact with TMV-MP30. Also, binding studies of MP30 with cell fractions enriched in plasmodesmal components indicate the presence of potential receptor molecules mediating protein movement via plasmodesmata (Kragler et al, 1998). Recently, Nt-NCAPP1, an ER-localized protein, was found to be involved in the plasmodesmal transport pathway of MP30 (Lee et al, 2003).…”
mentioning
confidence: 99%
“…Specific proteins have the capacity to dilate plasmodesmata, enabling large proteins, ribonucleoprotein complexes and viral particles to pass through (Lucas, 1999). Dilation of plasmodesmata is an active process triggered by the protein that is to be transported, and is reversed after its passage (Kragler et al, 1998). The plasmodesmal transport pathway appears to involve specific interactions between the non-cell-autonomous proteins and the plasmodesma, but the complexity of plasmodesmal regulation is still far from understood.…”
Section: Introductionmentioning
confidence: 99%